Sleep disordered breathing during live high-train low in normobaric versus hypobaric hypoxia - Saugy, J. J.; Schmitt, L.; Fallet, S.; Faiss, R.; Vesin, J.-M.; Bertschi, M.; Heinzer, R.; Millet, G. P. (High Altitude Medicine & Biology, 2016)
The present study aimed to compare sleep disordered breathing during live high-train low (LHTL) altitude camp using normobaric hypoxia (NH) and hypobaric hypoxia (HH). Sixteen highly trained triathletes completed two 18-day LHTL camps in a crossover designed study. They trained at 1100-1200 m while they slept either in NH at a simulated altitude of 2250 m or in HH. Breathing frequency and oxygen saturation (SpO2) were recorded continuously during all nights and oxygen desaturation index (ODI 3%) calculated. Breathing frequency was lower for NH than HH during the camps (14.6 ± 3.1 breath × min-1 vs. 17.2 ± 3.4 breath × min-1, p < 0.001). SpO2 was lower for HH than NH (90.8 ± 0.3 vs. 91.9 ± 0.2, p<?0.001) and ODI 3% was higher for HH than NH (15.1 ± 3.5 vs. 9.9 ± 1.6, p<?0.001). Sleep in moderate HH is more altered than in NH during a LHTL camp.